The Third Rome: dystopia and archaism as history of the present in Victor Pelevin’s Journey to Eleusis (Colloquia Comparativa Litterarum, 2025)
This article is an introduction to the close reading of Victor Pelevin’s novel Journey to Eleusis (2023) as a paradigmatical example of the Russian dystopian literature from the beginning of the 21th century. Journey to Eleusis is the final part of a trilogy whose previous installments include the collection of short novels Transhumanism Inc. (2021) that set the dystopian universe, and the sequel KGBT+ (2022) taking place already in the wartime sociopolitical reality. I argue that starting with Vladimir Sorokin’s Blue Lard (1999) the contemporary Russian dystopia intertwines idiosyncratically futurism and archaism into a retro-dystopian frame, which I discern in Pelevin’s trilogy. As I view it, this specific dystopian blend aims at the representation of a history of the present of the Putin era with its neo-totalitarian version of the Russian imperial concept of the “Third Rome” which is crucial to Journey to Eleusis.
Keywords: Russian dystopian literature; 21th century; archaism; retro-dystopia; The Third Rome; Victor Pelevin